Tablet containing boswellia serrata resin extract
By optimizing the formulation of tablets with Boswellia cerata resin extract, including specific ratios of crystalline cellulose and calcium stearate, and controlling hardness and reflectance, the challenges of color, ingestion ease, and disintegration time are addressed, resulting in improved tablet performance.
Patent Information
- Application Number
- JP2023166766
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Existing tablets containing Boswellia cerata resin extract face challenges in achieving a good balance between color appearance, ease of ingestion, and disintegration time, which are influenced by manufacturing conditions and ingredient ratios.
The tablets are formulated with Boswellia cerata resin extract, crystalline cellulose, and calcium stearate, with specific ratios of crystalline cellulose (50% or more by mass) and calcium stearate (1-10% by mass), along with controlled hardness (6-14 kgf), total reflectance (65% or more at 500 nm), and specular reflectance ratio (1.20 or less) to optimize color and disintegration time.
This formulation enables tablets with improved color appearance and disintegration time, enhancing their ease of ingestion and manufacturing stability, while maintaining the effectiveness of the Boswellia cerata resin extract.
Smart Images

Figure 2025057099000002 
Figure 2025057099000003 
Figure 2025057099000001
Abstract
Description
[Technical field]
[0001] The present invention relates to tablets containing Boswellia serrata resin extract. [Background technology]
[0002] In recent years, the demand for supplements containing amino acids, vitamins, and various plant-derived extracts has increased due to the growing health consciousness. The most popular dosage form of supplements is tablets, which are highly portable and can be easily taken. The appearance of tablets is influenced by the origin of the raw materials used, and the size of the tablets can affect the ease of taking them.
[0003] Boswellia serrata, a member of the Boswellia genus, has been used in the traditional Indian medicine Ayurveda for the treatment of rheumatism, arthritis, and hyperlipidemia using essential oils extracted from the resin. Boswellia serrata resin contains β-boswellic acid, acetyl-β-boswellic acid, 11-keto-β-boswellic acid, and 3-O-acetyl-11-keto-β-boswellic acid (AKBA), among others.
[0004] As a supplement containing Boswellia serrata resin, Kobayashi Pharmaceutical Glucosamine EX (trade name) is known. Kobayashi Pharmaceutical Glucosamine EX (trade name) (Non-Patent Document 1) is a tablet containing Boswellia serrata resin extract, crystalline cellulose, calcium stearate, etc. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] https: / / www.kobayashi.co.jp / brand / syokuhin / supplement / gluco_ex / Summary of the Invention [Problem to be solved by the invention]
[0006] Generally, tablets are desirable to have a good appearance, be small and easy to swallow. Furthermore, the disintegration time of the tablet is important from the viewpoint of exerting the effect of the ingredient. For supplements containing 3-O-acetyl-11-keto-β-boswellic acid, it is desirable to have a short disintegration time from the viewpoint of exerting the effect of the ingredient.
[0007] The appearance, size, disintegration time, etc. of a tablet can be determined by blending functional ingredients, excipients, disintegrants, etc. at the tablet design stage. However, even if the content of each ingredient is constant, the appearance, size, and disintegration time may change depending on the manufacturing conditions of the tablet press. From the viewpoint of product quality and manufacturing stability, it is desirable to match the manufacturing conditions as much as possible between product lots to minimize the differences in the appearance, size, and disintegration time of the tablets.
[0008] In tablet production, the hardness of the tablet varies depending on the pressure applied during tableting (tabletting pressure), so the hardness is sometimes controlled during production. The lower the tableting pressure, the lower the hardness, and the higher the tableting pressure, the higher the hardness.
[0009] When the content of each component is constant, at low hardness, the tableting pressure is low, so the tablet thickness increases, which may make it difficult to take the tablet. The disintegration time tends to be short, and the color of the tablet may not be colored from the raw materials. To ensure ease of handling, the mass can be improved to make the tablet smaller, but this method may increase the number of particles, which may increase the burden on the user and increase the manufacturing cost. On the other hand, at high hardness, the tableting pressure is high, so the tablet thickness decreases, making it easier to take. However, because the tablet is compressed strongly, the disintegration time increases, and the color of the tablet may become more colored from the raw materials.
[0010] An object of the present invention is to provide a tablet containing a Boswellia serrata resin extract, which has good color and disintegration time. [Means for solving the problem]
[0011] The present inventors have conducted extensive research to solve the above problems, and evaluated tablets by combining optical analysis with sensory evaluation (ease of ingestion, tablet color). As a result, the present inventors have found that tablets with good color and disintegration time can be provided by setting the tablet hardness, total reflectance at a wavelength of 500 nm, and specular reflection intensity ratio within a predetermined range. The present invention was completed based on the above findings.
[0012] That is, according to the present invention, the following inventions are provided. <1> A tablet containing Boswellia serrata resin extract, microcrystalline cellulose and calcium stearate, The content of crystalline cellulose in the tablet is 50% by mass or more, and the content of calcium stearate in the tablet is 1% by mass or more and 10% by mass or less, The hardness is 6 to 14 kgf, the total reflectance at a wavelength of 500 nm is 65% or more, and the specular reflection intensity ratio is 1.20 or less. tablet. <2> The surface roughness is 2.1 μm or less. <1> The tablet described in. <3> The thickness is 6.2 mm or less, <1> or <2> The tablet described in. <4> In the tablet disintegration test method listed in the 18th Edition of the Japanese Pharmacopoeia, the disintegration test liquid is ion-exchanged water, and the disintegration time is 60 minutes or less when the water bath temperature is 37°C. <1> ~ <3> A tablet according to any one of the preceding claims. <5> Further, the composition contains at least one of salmon nasal cartilage extract and olive leaf extract. <1> ~ <4> A tablet according to any one of the preceding claims. Effect of the Invention
[0013] According to the present invention, it is possible to provide a tablet containing a Boswellia serrata resin extract, which has good color and disintegration time. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a diagram showing the configuration of an apparatus used to measure specular reflectance. [Diagram 2] FIG. 2 is a diagram showing the configuration of an apparatus used to measure the total reflectance at each wavelength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below. In this specification, a numerical range indicated using "to" means a range including the numerical values before and after "to" as the minimum and maximum values, respectively.
[0016] [Tablet composition] The tablet of this embodiment is a tablet containing Boswellia serrata resin extract, crystalline cellulose and calcium stearate, The content of crystalline cellulose in the tablet is 50% by mass or more, and the content of calcium stearate in the tablet is 1% by mass or more and 10% by mass or less, The hardness is 6 to 14 kgf, the total reflectance at a wavelength of 500 nm is 65% or more, and the specular reflection intensity ratio is 1.20 or less. It is a tablet. In this embodiment, for a tablet containing Boswellia serrata resin extract, good hardness conditions and optical numerical conditions were found to provide ease of ingestion, tablet color, and disintegration time.
[0017] Boswellia serrata resin extract is commercially available, for example from Sabinsa Japan Corporation and TS Trading Co., Ltd. Boswellia serrata resin extract mainly contains 3-O-acetyl-11-keto-β-boswellic acid.
[0018] The content of the Boswellia serrata resin extract in the tablet is not particularly limited, but is preferably 5.0 to 45.0% by mass, more preferably 10.0 to 35.0% by mass. By making the content of the Boswellia serrata resin extract relative to the total mass of the tablet 5.0% by mass or more, the number of tablets to be taken at one time can be reduced. By making the content of the Boswellia serrata resin extract relative to the total mass of the tablet 45.0% by mass or less, it becomes easy to mix with other raw materials.
[0019] Crystalline cellulose is produced, for example, from trees and tree trunks. Crystalline cellulose is commercially available, for example, Ceolus FD-101, FD-301, FD-F20, and ST-02 (manufactured by Asahi Kasei Corporation), and crystalline cellulose FD-101 is preferably used.
[0020] From the viewpoint of suppressing the decrease in dispersibility of the contents and maintaining the stability of AKBA, the content of crystalline cellulose in the tablet is 50% by mass or more, preferably 55% by mass or more, and more preferably 60% by mass or more. The upper limit of the content of crystalline cellulose relative to the total mass of the tablet is not particularly limited, but is generally 80% by mass or less. The content of crystalline cellulose relative to the total mass of the tablet is preferably 50 to 70% by mass.
[0021] Calcium stearate is commercially available, for example from Taihei Chemical Industry Co., Ltd.
[0022] From the viewpoint of improving the fluidity of the mixed powder, the content of calcium stearate in the tablet is from 1% by mass to 10% by mass, preferably from 2% by mass to 10% by mass, and more preferably from 4% by mass to 8% by mass.
[0023] The hardness of the tablet is 6 to 14 kgf, preferably 7 to 13 kgf, and more preferably 8 to 12 kgf. By having the hardness within the range of 6 to 14 kgf, good disintegration time and good swallowability can be achieved. The tablet hardness can be measured using a commercially available hardness tester that can measure the hardness of tablets. For example, it can be measured using a digital hardness tester (KHT-40N, Fujiwara Seisakusho Co., Ltd.). The tablet hardness is measured for 10 tablets and the average value is calculated.
[0024] In the tablet of this embodiment, the total reflectance at a wavelength of 500 nm, which is the blue to green wavelength, is 65% or more, and more preferably 73% or more. The total reflectance at 400 nm, which is a violet wavelength, is preferably 51% or more, and more preferably 59% or more. The total reflectance at 600 nm, which is a wavelength of yellow to orange, is preferably 79% or more, and more preferably 86% or more. The total reflectance at 700 nm, which is the red wavelength, is preferably 90% or more, and more preferably 94% or more.
[0025] As mentioned above, 500nm is a blue to green wavelength, 400nm is a purple wavelength, 600nm is a yellow to orange wavelength, and 700nm is a red wavelength. The low reflectance of each wavelength indicates that the wavelength is absorbed. The reflectance at each wavelength can be measured using a commercially available device capable of measuring reflectance. As described in the Examples below, for example, it can be measured using the device shown in Figure 2. The reflectance at each wavelength is measured three times and the average value is calculated.
[0026] In the tablet of this embodiment, the specular reflection intensity ratio is 1.20 or less, preferably 1.15 or less. The lower limit of the specular reflection intensity ratio is not particularly limited, but is preferably 1.00 or more. The specular reflection intensity ratio is a measurement of the degree of reflection of light incident at 30° when viewed from the front, and is the reflectance of light on the tablet surface. If the reflectance is low, it can be seen that the incident light is scattered by the tablet surface. In other words, the specular reflection intensity ratio is a value related to the color of the tablet. The specular reflection intensity ratio can be measured using a commercially available device capable of measuring the specular reflection intensity ratio. As described in the Examples below, the measurement can be performed using, for example, the device shown in Figure 1. The specular reflection intensity ratio is measured three times and the average value is calculated.
[0027] <Surface roughness> The surface roughness is a value related to swallowability, and is preferably 2.1 μm or less, more preferably 1.3 μm or less. The lower limit of the surface roughness is not particularly limited, but is preferably 0.7 μm or more, more preferably 0.9 μm or more, and even more preferably 1.1 μm or more. The surface roughness can be measured using a commercially available device capable of measuring surface roughness. As described in the Examples below, for example, it can be measured using a confocal laser microscope. The surface roughness is measured twice and the average value is calculated.
[0028] <Tablet thickness> The thickness of the tablet is a value related to swallowability and is preferably 6.2 mm or less, more preferably 5.9 mm or less. The lower limit of the thickness of the tablet is not particularly limited, but is preferably 5.4 mm or more, more preferably 5.5 mm or more. The thickness of a tablet is the height of the tablet in a side view, which is the thickest part of the tablet. The thickness of a tablet is measured by measuring 10 tablets using a vernier caliper or the like, and the maximum value is used.
[0029] The disintegration property of a tablet can be evaluated in the tablet disintegration test method described in the 18th Edition of the Japanese Pharmacopoeia, using ion-exchanged water as the disintegration test liquid and setting the water bath temperature at 37° C. The disintegration time under these evaluation conditions is preferably 60 minutes or less, more preferably 30 minutes or less. The lower limit of the disintegration time is not particularly limited, but is generally 5 minutes or more.
[0030] The tablet of this embodiment may further contain one or more of salmon nasal cartilage extract and olive leaf extract as optional active ingredients.
[0031] Olive leaf extract is commercially available, for example from Mitsubishi Chemical Corp. Olive leaf extract contains hydroxytyrosol derived from olives.
[0032] When olive leaf extract is used, the content of the olive leaf extract relative to the total mass of the tablet is preferably 0.5 to 10 mass%, more preferably 0.6 to 8 mass%, and even more preferably 1 to 6 mass%.
[0033] Salmon nasal cartilage extract is commercially available, for example, from Nippon Yakuhin Co., Ltd. The salmon nasal cartilage extract contains salmon nasal cartilage-derived proteoglycan and salmon nasal cartilage-derived non-denatured type II collagen as functional ingredients.
[0034] When salmon nasal cartilage extract is used, the content of the salmon nasal cartilage extract relative to the total mass of the tablet is preferably 0.5 to 10 mass%, more preferably 0.6 to 5 mass%, and even more preferably 0.8 to 3 mass%.
[0035] The tablet of this embodiment may contain the optional ingredients described below. Optional ingredients include, but are not limited to, excipients, lubricants, disintegrants, and the like.
[0036] Examples of excipients include lactose, lactose granules, starch, granulated sugar, mannitol, magnesium carbonate, calcium carbonate, refined sucrose, glucose, hydrated glucose, silicon dioxide (also known as silicic acid anhydride, fine silicon dioxide), low-substituted hydroxypropyl cellulose, L-cysteine, methylethyl cellulose, etc., with fine silicon dioxide being more preferred.
[0037] When an excipient is included, its content (total amount when two or more excipients are used) is usually 0.5% by mass or more, preferably 1.0% by mass or more, more preferably 1.5% by mass, based on the total mass of the tablet. This can further reduce tableting problems. The upper limit of the content of the excipient is not particularly limited, but is generally 10% by mass or less, and may be 5% by mass or less.
[0038] In this embodiment, calcium stearate is used as a lubricant, but a lubricant other than calcium stearate may be used. By containing a lubricant, friction can be reduced. Examples of lubricants other than calcium stearate include metal stearates (e.g., magnesium stearate), sodium stearyl fumarate, and sucrose fatty acid esters, and sucrose fatty acid esters are more preferred.
[0039] The content of the lubricant (total amount including the content of calcium stearate) is 1% by mass or more, preferably 4% by mass or more, more preferably 6% by mass, based on the total mass of the tablet. This improves the fluidity of the raw material and can further reduce tableting problems. However, since the moldability is deteriorated, the pressure during tableting increases and the disintegration time becomes longer, a disintegrant may be used. The upper limit of the content of the lubricant is not particularly limited, but is generally 20% by mass or less, and may be 10% by mass or less.
[0040] Examples of disintegrants include agar for disintegrants, hydroxypropyl cellulose, carboxymethylcellulose (carmellose), sodium carboxymethylcellulose (carmellose sodium, CMC-Na), calcium carboxymethylcellulose (also known as carmellose calcium, CMC-Ca), croscarmellose sodium, cross-linked insoluble polyvinylpyrrolidone, crospovidone, pregelatinized starch, sodium starch glycolate, etc. From the viewpoint of further improving disintegration properties, calcium carboxymethylcellulose, carboxymethylcellulose, sodium carboxymethylcellulose, pregelatinized starch, sodium starch glycolate are preferred, calcium carboxymethylcellulose, pregelatinized starch, sodium starch glycolate are more preferred, and sodium starch glycolate is particularly preferred.
[0041] When a disintegrant is included, its content (when two or more kinds of disintegrants are used, the total amount) is usually 1% by mass or more, preferably 2% by mass or more, based on the total mass of the tablet. This can further reduce tableting problems. The upper limit of the content of the disintegrant is not particularly limited, but is generally 20% by mass or less, and may be 15% by mass or less.
[0042] Specific examples of the tablet of this embodiment include the following tablets. Tablets containing Boswellia serrata resin extract, olive leaf extract, salmon nasal cartilage extract, crystalline cellulose, sodium starch glycolate, fine silicon dioxide, calcium stearate, and sucrose fatty acid esters.
[0043] [Tablet manufacturing method] The method for producing the tablet of the present embodiment is not particularly limited, and any known method can be used. The tablets can be produced, for example, by mixing essential ingredients and optional ingredients (hereinafter referred to as a "mixing step"), followed by a granulation step and tableting.
[0044] <Mixing process> The mixing step is not particularly limited, and the raw materials of Boswellia serrata resin extract, crystalline cellulose, calcium stearate and optional components are mixed. The mixing method is not particularly limited, and examples of the mixers used in these mixing methods include tumbler mixers, V-type mixers, double cone mixers, stirring mixers, high-speed fluid mixers, drum mixers, fluidized bed mixers, and infinite mixers.
[0045] <Granulation process> The granulation step is not particularly limited, and examples thereof include wet granulation, dry granulation, heat granulation, spray granulation, etc. Preferably, a direct compression method is used in which the mixture is compressed directly after the mixing step without performing a granulation step.
[0046] <Tableting process> The tableting step is not particularly limited and may be carried out by a commonly used method, for example, by using a rotary tablet press. As for the pressure during filling and pressurization in the tableting process, the tableting pressure applied to the punch part of the tableting machine is preferably 2.5 kN to 9.2 kN, more preferably 3.8 kN to 6.0 kN. If the pressure is less than 2.5 kN, sufficient hardness cannot be obtained, and the tablet may become brittle or sticking may occur, while if it exceeds 9.3 kN, capping may occur. By setting the pressure at 9.2 kN or less, the hardness is 14 kgf or less and the disintegration time is 60 minutes or less, which is preferable.
[0047] <Coating> Coating can improve the appearance of the tablet and the odor derived from the raw materials, but it can also increase production costs and has poor compatibility with some raw materials. Therefore, the tablet of this embodiment is preferably an uncoated plain tablet.
[0048] <Tablet shape> The shape of the tablet is not particularly limited as long as it is one used in the technical fields of medicines, quasi-drugs, cosmetics, food, feed, etc. Examples of the shape of the tablet include round tablets, oval tablets, flower-shaped tablets, etc., and round tablets are preferred.
[0049] <Tablet Uses and Usage> The use of the tablet of this embodiment is not particularly limited, and it can be used as a food composition or a pharmaceutical composition (such as a drug or quasi-drug), but it is preferably used as a food composition. The tablet of this embodiment is preferably administered orally.
[0050] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples. EXAMPLES
[0051] <1> Formulation and dosage of tablets containing Boswellia serrata resin extract Boswellia serrata resin extract: NEO Frankincense (Sabinsa Japan Corporation), 20.83% by mass Olive leaf extract: Oralis (Mitsubishi Chemical Corporation), 4.17% by mass Salmon nasal cartilage extract: Proteoglycan HG-100 (Nihon Yakuhin Co., Ltd.), 2.08% by mass Crystalline cellulose: Ceolus FD-101 (Asahi Kasei Corporation), 62.92% by mass Sodium starch glycolate: Sodium starch glycolate (Phytopharma Co., Ltd.), 2.00% by mass Fine silicon dioxide: SYLOPAGE720 (Fuji Silysia Chemical Ltd.), 1.50% by mass Calcium stearate: Calcium stearate (Taihei Chemical Industry Co., Ltd.), 6.00% by mass Sucrose fatty acid ester: Ryoto Sugar Ester S-1670 (Mitsubishi Chemical Corporation), 0.50% by mass
[0052] <2> Tablet manufacturing After mixing the above components, the mixture was compressed in a rotary tablet press under the conditions described in the following Comparative Examples 1 to 3 and Examples 1 to 3, and then packed and compressed in a conventional manner to obtain round tablets of various hardness with a diameter of 9 mm, a radius of curvature (R) of 7.5 mm, and a weight of 300 mg per tablet. All tablets were uncoated.
[0053] Comparative Example 1 The powder for tableting was compressed at a pressure of 2.4 kN to obtain tablets with a hardness of 5 kgf. Comparative Example 2 The powder for tableting was compressed at a pressure of 9.3 kN to obtain tablets with a hardness of 15 kgf. Comparative Example 3 The powder for tableting was compressed at a pressure of 15.1 kN to obtain tablets with a hardness of 17 kgf.
[0054] Example 1 The powder for tableting was compressed at a pressure of 3.8 kN to obtain tablets with a hardness of 8 kgf. Example 2 The powder for tableting was compressed at a pressure of 4.8 kN to obtain tablets with a hardness of 10 kgf. Example 3 The powder for tableting was compressed at a pressure of 6.0 kN to obtain tablets with a hardness of 12 kgf.
[0055] <3> Tablet evaluation <Tablet hardness measurement> Tablet hardness was measured using a digital hardness tester (KHT-40N, Fujiwara Seisakusho Co., Ltd.) (10 tablets were measured and the average value was calculated).
[0056] <Measurement of disintegration> The disintegration of the tablets was performed according to the tablet disintegration test method listed in the 18th Edition of the Japanese Pharmacopoeia, using ion-exchanged water as the disintegration test liquid and a water bath temperature of 37° C. In terms of the effectiveness of the ingredients, the disintegration time under these evaluation conditions is preferably less than 60 minutes, and more preferably less than 30 minutes.
[0057] <Tablet thickness measurement> The height of the tablet in the side view of the tablet, which is the thickest part of the tablet. Ten tablets were measured using a vernier caliper, and the maximum value was recorded.
[0058] <Evaluation of tablet swallowability> The ease of swallowing felt by the users in terms of daily intake was ranked from "no burden when swallowing" to "feeling burden when swallowing" with A, B, or C.
[0059] <Evaluation of tablet color> The color of the tablet surface was evaluated based on two items: "color brightness" and "color dullness." For "color brightness," the tablet color was rated from light to dark, with a score of 1 to 3. For "dullness," the tablet color was rated from no dullness to dullness, with a score of 1 to 3. The color and dullness ratings were added together, and 2 to 3 points were given an A, 4 points a B, and 5 points or more a C.
[0060] <Surface roughness measurement> The tablet surfaces were measured using a confocal laser microscope. The laser emitted from the laser light source scans the surface of the tablet, recording the amount of reflected light data that enters the surface in the X and Y directions, as well as the value in the Z direction (vertical). After recording, the Z (vertical) direction is moved, and the amount of reflected light data that enters the surface in the X and Y directions, as well as the value in the Z direction, are similarly recorded. The point where the reflected light is at its maximum is considered to be in focus, and by connecting the X, Y point where the reflected light is at its maximum with the lens height (Z direction), the tablet's surface unevenness can be measured. This is called the surface roughness. This time, the height (Z direction) was recorded from -10μm to 10μm relative to the reference height, and the average value of the average height difference from the reference surface was taken as the average roughness (Ra). Each hardness was measured twice, and the average result was used.
[0061] <Specular reflection intensity ratio measurement> FIG. 1 is a diagram showing the configuration of an apparatus used to measure the specular reflection intensity ratio. The light emitted from the light source 11 has a wavelength of 543 nm, and the center of the curved surface of a tablet, which is the sample 13 attached to the irradiation table 12, is the irradiation position. As shown in angle A 14, the irradiation table 12 and the sample 13 are irradiated at 30° when viewed from the front. The reflectance was measured while moving the detector 15 from the front to angles B 16 from 0° to 90° and angles C 17 from -90° to 0°. Measurements were made three times for each hardness, and the average value was obtained. The value at an angle of 0° was set to 1, and taking into account that the reflection angle varies depending on the curvature or roughness of the sample surface, the maximum value in the range of -30°±10°, i.e., -40° to -20°, was taken as the specular reflection intensity ratio.
[0062] <Measurement of reflectance at each wavelength> FIG. 2 is a diagram showing the configuration of the device used to measure the total reflectance. The light source 21 is a Xe lamp, and the light irradiated from the light source is collected by a lens 22, and the light is irradiated onto a tablet sample 26 through a pinhole 23, a lens 24, and an aperture stop 25. The light reflected from the tablet is measured by an integrating sphere 27, and the total light reflected from the sample is measured by a spectrometer 29 through an optical fiber 28. The reflectance of each wavelength from 400 nm to 800 nm was measured by an integrating sphere using a white diffuser as a reference. This reflects diffuse reflection and specular reflection, and this was taken as the total reflectance of each wavelength. For each hardness, measurements were taken three times, and the average value was obtained.
[0063] The evaluation results are summarized in Table 1.
[0064] [Table 1]
[0065] In Comparative Example 1, the tablet thickness was 6.3 mm, the swallowability was rated as bad (rated C), and the color was rated as good (rated A). The surface roughness was 2.2 μm, the specular reflection intensity ratio was 0.96, the reflectance at a wavelength of 500 nm was 76%, and the disintegration time was 30 minutes or less. In Comparative Example 2, the tablet had a thickness of 5.3 mm, and the swallowability was evaluated as good (evaluation A), but the color was evaluated as bad (evaluation C). The surface roughness was 0.5 μm, the specular reflection intensity ratio was 1.21, the total reflectance at a wavelength of 500 nm was 64%, and the disintegration time was 60 minutes or less. In Comparative Example 3, the tablet had a thickness of 5.2 mm, and the swallowability was evaluated as good (evaluation A), but the color was evaluated as bad (evaluation C). The surface roughness was 0.6 μm, the specular reflection intensity ratio was 1.59, the total reflectance at a wavelength of 500 nm was 61%, and the disintegration time was 60 minutes or more.
[0066] In Example 1, the tablet had a thickness of 5.9 mm, was rated as good for both swallowability and color (rating A), had a surface roughness of 1.2 μm, a specular reflection intensity ratio of 1.05, a total reflectance at a wavelength of 500 nm of 76%, and a disintegration time of 30 minutes or less. In Example 2, the tablet had a thickness of 5.7 mm, was rated as good for both swallowability and color (rating A), had a surface roughness of 1.1 μm, a specular reflection intensity ratio of 1.12, a total reflectance at a wavelength of 500 nm of 74%, and a disintegration time of 30 minutes or less. In Example 3, the tablet had a thickness of 5.5 mm, was rated as good for both swallowability and color (rating A), had a surface roughness of 1.3 μm, a specular reflection intensity ratio of 1.15, a total reflectance at a wavelength of 500 nm of 73%, and a disintegration time of 60 minutes or less.
[0067] If the total reflectance of 500 nm, which is the blue wavelength, is 64% or less, the tablet will strongly reflect brown to red due to the absorption of blue wavelengths. Furthermore, the specular reflection intensity ratio reflects the reflection from the light incident on the tablet, and if the specular reflection intensity ratio is 1.21 or more, the tablet color will be emphasized, which is associated with a deterioration in the tablet color evaluation. Surface roughness indicates the numerical value of the unevenness on the tablet surface; a surface roughness of 2.2 μm and a tablet thickness of 6.3 mm will lead to poor swallowability. From the above, if the total reflectance at 500 nm (blue wavelength) is 65% or more and the specular reflection intensity ratio is 1.20 or less, the color evaluation of the tablet can be improved. Furthermore, if the surface roughness is 2.1 μm or less and the tablet thickness is 6.2 mm or less, the swallowability can be improved. These results indicate that by optimizing the tableting adjustments for the same formulation, it is possible to produce supplements that are optimal for consumers.
[0068] (Reference example) For Kobayashi Pharmaceutical Glucosamine EX (trade name), the surface roughness, specular reflection intensity ratio, and total reflectance at a wavelength of 500 nm were measured in the same manner as in Example 1. The results were as follows: surface roughness 1.7 μm, specular reflection intensity ratio 1.07, total reflectance at a wavelength of 500 nm 59%. [Explanation of symbols]
[0069] 11 Light source 12 Irradiation table 13 Sample 14 Angle A 15 Detector 16 Angle B 17 Angle C 21 Light source 22 Lens 23 Pinhole 24 Lenses 25 Aperture 26 Samples 27 Integrating Sphere 28 Optical Fiber 29 Spectrometer
Claims
1. A tablet containing Boswellia serrata resin extract, microcrystalline cellulose and calcium stearate, The content of crystalline cellulose in the tablet is 50% by mass or more, and the content of calcium stearate in the tablet is 1% by mass or more and 10% by mass or less, The hardness is 6 to 14 kgf, the total reflectance at a wavelength of 500 nm is 65% or more, and the specular reflection intensity ratio is 1.20 or less. tablet.
2. 2. The tablet according to claim 1, having a surface roughness of 2.1 μm or less.
3. 3. The tablet according to claim 1 or 2, having a thickness of 6.2 mm or less.
4. 3. The tablet according to claim 1 or 2, wherein the disintegration time is 60 minutes or less when ion-exchanged water is used as a disintegration test liquid and the water bath temperature is 37°C in the tablet disintegration test method described in the Japanese Pharmacopoeia, 18th Edition.
5. 3. The tablet of claim 1 or 2, further comprising one or more of a salmon nasal cartilage extract and an olive leaf extract.